IMAM PARA NABI: MENELUSUR JEJAK KEPEMIMPINAN DAN MANAJERIAL NABI MUHAMMAD SAW - Umam, Muhammad Khoirul (Jurnal al Hikmah, 2018)
In Islamic thought, the model leaders are simultaneously both managerial and vision, mission and inspiration, but at the same time dedicated to serving the general public. The purpose of this study, the author discusses the ideal leadership and important attributes of a leader such as managerial, courage, integrity, practical wisdom, and moral authority and humility. So that raises the question of research on the leadership of the Prophet Muhammad in western management theory. To answer this research question, researchers collected data through documentation methods. Then after the data is collected, it is analyzed through content analysis and critical analysis. So that this study resulted in one of the offerings of thought about an improvement model and changes in innovative leadership and management